Pagan in exile - Jinks, Catherine (London Collins, 2004)
After fighting the infidels in Jerusalem in 1188, Lord Roland and his squire Pagan return to Roland's castle in France where they encounter violent family feuds and religious heretics.
530
Accelerated Reader AR
Keywords: Knights and knighthood -- Fiction; Orphans -- Fiction; Religious life -- Fiction; Heretics, Christian -- Fiction; Middle Ages -- Fiction; France -- History -- Medieval period, 987-1515 -- Fiction